Complications Associated with Image-Guided Percutaneous Thermal Ablation of Liver Tumors - Arellano, Ronald S. (Digestive Disease Interventions, 2023)
Image-guided thermal ablation of liver cancer is a well-established treatment for patients with primary or secondary liver tumors. While the safety profile for liver ablations is high, several procedure-related complications can occur. An awareness of the potential complications, their recognition, and management are essential for the interventionist who performs liver ablation. This review will describe some of the most frequently encountered complications associated with image-guided thermal ablation of hepatic malignancies.
Keywords: hepatocellular carcinoma; colorectal metastasis; complications